Association of HLA genotypes with phenobarbital hypersensitivity in children. (24th August 2016) - Manuyakorn, Wiparat; Mahasirimongkol, Surakameth; Likkasittipan, Plernpit; Kamchaisatian, Wasu; Wattanapokayakit, Sukanya; Inunchot, Wimala; Visudtibhan, Anannit; Wichukchinda, Nuanjun; Benjaponpitak, Suwat
Summary: Objective: Phenobarbital hypersensitivity is one of the common drug hypersensitivity syndromes in children. Clinical symptoms of phenobarbital hypersensitivity vary from maculopapular rashes (MPs) to severe cutaneous adverse drug reactions (SCARs) including drug reactions with eosinophilia and systemic symptoms (DRESS), Stevens‐Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN). Drug hypersensitivity has been demonstrated to be associated with variations in the HLA genotypes. This study was to investigate the association between the variations of HLA genotypes and phenobarbital hypersensitivity in Thai children. Methods: The cases were Thai children, between 0 and 18 years of age, who were diagnosed with phenobarbital hypersensitivity, which included SCARs and MPs. The control patients were Thai children of a corresponding age who had taken phenobarbital for at least 12 weeks without any hypersensitivity reaction. Blood samples were collected for HLA genotyping by using a reverse‐sequence‐specific oligonucleotide (SSO) probes method. The carrier rates of HLA alleles were compared between 47 cases (27 SCARs and 20 MPs) and 54 controls. Results: The carrier rates of HLA‐A*01:01 and HLA‐B*13:01 were significantly higher in the phenobarbital‐induced SCARs than in the tolerant controls (18.5% vs. 1.85%, p = 0.01, odds ratio [OR] 11.66, 95% confidence interval [CI] 1.21–578.19; 37.04% vs. 11.11%, p = 0.009, OR 4.60, 95%CI 1.29–17.98). There was a trend of a higher carrier rate of HLA‐C*06:02 in the phenobarbital‐induced SCARs when compared with those in the tolerant controls (29.63% vs. 11.11%, p = 0.059, OR 3.31, 95% CI 0.88–13.31). In contrast to the phenobarbital‐induced SCARs, only the HLA‐A*01:01 carrier rate in the phenobarbital‐induced MPs was significantly higher than those in the tolerant controls (20% vs. 1.85%, p = 0.017, OR 12.69, 95% CI 1.15–661.62). Significance: An association between phenobarbital hypersensitivity and HLA‐A*01:01 and HLA‐B*13:01 has been demonstrated in Thai children.